Inflasi Makanan dan Implikasinya terhadap Kebijakan Moneter di Indonesia - Pratikto, Rulyusa; Ikhsan, Mohamad (Jurnal Ekonomi dan Pembangunan Indonesia, 2016)
Controlling food inflation in Indonesia is essential mainly caused by its persistent and relatively significant impact on the poor’s purchasing power compare to other commodities. Thus, the main purpose of this study is to determine the effectiveness of monetary policy on food inflation stabilization in Indonesia. By utilizing Structural Vector Autoregression, the empirical results provided here show that monetary policy does effectively prevent the spillover effect of food to non-food inflation. In addition to that, the exchange rate may play some role in the longer period to affect the volatility of food inflation.